Las Humanidades e Internet - Alvite Díez, María Luisa; Morán Suárez, María Antonia (Estudios humanísticos. Geografía, historia y arte, 1999)
This paper examines the model of seeking’s the humanits scholars, as the current state and developement of specialized, internet-based resources in the humanities. The selection of the informatin resources in this field is presented and evaluated.